2017
DOI: 10.1007/s13312-017-1090-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of SNAPPS model for pediatric outpatient education

Abstract: SNAPPS promotes clinical reasoning and self-directed learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…To our knowledge, SNAPPS has not been studied in the PED setting. However, consistent with the results of the present study, a previous study which assessed the use of SNAPPS in paediatric outpatient training of residents found that residents presented more differential diagnoses, raised uncertainties more often by probing preceptors and selected case‐related issued for self‐study more often with SNAPPS compared to ‘traditional’ case presentations . A study in which SNAPPS was used to teach child psychiatry fellows and third year general psychiatry residents in an outpatient child psychiatry clinic showed that the learners were highly satisfied with the method .…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, SNAPPS has not been studied in the PED setting. However, consistent with the results of the present study, a previous study which assessed the use of SNAPPS in paediatric outpatient training of residents found that residents presented more differential diagnoses, raised uncertainties more often by probing preceptors and selected case‐related issued for self‐study more often with SNAPPS compared to ‘traditional’ case presentations . A study in which SNAPPS was used to teach child psychiatry fellows and third year general psychiatry residents in an outpatient child psychiatry clinic showed that the learners were highly satisfied with the method .…”
Section: Discussionsupporting
confidence: 89%
“…This model has been shown to increase the confidence in preceptors' teaching and is designed for educators of all experience levels and backgrounds. 99 Aside from demonstrating an increased knowledge of teaching strategies specific to the ED, this technique has also been associated with an increased satisfaction and confidence in teaching abilities by the individual. 99…”
Section: E Ed Stat (Emergency Department Strategies For Teaching Anymentioning
confidence: 99%
“…A small study done in pediatrics outpatient demonstrated the effectiveness of SNAPPS as a method of case presentation which improved clinical reasoning. The resident in the study perceived that the SNAPPS model was more structured, stimulating and relevant to teaching in out-patient department (OPD), was easy to follow and made them motivated for self-learning [5]. There has been only a handful cursory research utilizing SNAPPS for inpatient learning which provides a wonderful teaching learning opportunity [2].…”
Section: Introductionmentioning
confidence: 99%